Fructan oligosaccharide priming alters apoplastic sugar dynamics and improves resistance against Botrytis cinerea in chicory - TOKSOY ÖNER, EBRU (My University, 2022)
Carbohydrates such as fructans can be involved in priming or defence stimulation, and hence potentially provide new strategies for crop protection against biotic stress. Chicory (Cichorium intybus) is a model plant for fructan research and is a crop with many known health benefits. Using the chicory–Botrytis cinerea pathosystem, we tested the effectiveness of fructan-induced immunity, focussing on different plant and microbial fructans. Sugar dynamics were followed after priming and subsequent pathogen infection. Our results indicated that many higher plants might detect extracellular levan oligosaccharides (LOS) of microbial origin, while chicory also detects extracellular small inulin-type fructooligosaccharides (FOS) of endogenous origin, thus differing from the findings of previous fructan priming studies. No clear positive effects were observed for inulin or mixed-type fructans. An elicitor-specific burst of reactive oxygen species was observed for sulfated LOS, while FOS and LOS both behaved as genuine priming agents. In addition, a direct antifungal effect was observed for sulfated LOS. Intriguingly, LOS priming led to a temporary increase in apoplastic sugar concentrations, mainly glucose, which could trigger downstream responses. Total sugar and starch contents in total extracts of LOS-primed leaves were higher after leaf detachment, indicating they could maintain their metabolic activity. Our results indicate the importance of balancing intra- and extracellular sugar levels (osmotic balance) in the context of ‘sweet immunity’ pathways.
Keywords: Tarımsal Bilimler; Ziraat; Bitki Koruma; Fitopatoloji; Agricultural Sciences; Agriculture; Plant Protection; Phytopathology; BİTKİ BİLİMLERİ; Bitki ve Hayvan Bilimleri; Tarım ve Çevre Bilimleri (AGE); PLANT SCIENCES; PLANT & ANIMAL SCIENCE; Agriculture & Environment Sciences (AGE); Bitki Bilimi; Küçük hayvanlar; Yaşam Bilimleri; Sağlık Bilimleri; Plant Science; Small Animals; Life Sciences; Health Sciences; Apoplast; Botrytis cinerea; Cichorium intybus; fructan; levan oligosaccharide; priming; sugars; sweet immunity; SNOW MOLD RESISTANCE; DEFENSE RESPONSES; ARABIDOPSIS-THALIANA; MOLECULAR-PATTERNS; IMMUNE-RESPONSES; OXIDATIVE BURST; SWEET IMMUNITY; WHEAT; LEVAN; SUCROSE